2018
DOI: 10.1186/s12885-018-5023-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PKM2 on global metabolic changes and prognosis in hepatocellular carcinoma: from gene expression to drug discovery

Abstract: BackgroundHepatocellular carcinoma (HCC) is a malignant tumor that threatens global human health. High PKM2 expression is widely reported in multiple cancers, especially in HCC. This study aimed to explore the effects of PKM2 on global gene expression, metabolic damages, patient prognosis, and multiple transcriptional regulation relationships, as well as to identify several key metabolic genes and screen some small-molecule drugs.MethodsTranscriptome and clinical HCC data were downloaded from the NIH-GDC repos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…According to the Warburg effect, most cancer cells produce energy by glycolysis, suggesting that targeting cancer metabolism might be a potential field in drug discovery (Liu et al, 2016;Lv et al, 2018;Yang et al, 2017). As a key regulator involving in Warburg effect, PKM2 is frequently expressed at high levels in numerous human tumors and play an important role in tumorigenesis, aerobic glycolysis and chemoresistance (Dayton, Jacks & Vander Heiden, 2016;Guo et al, 2019;Liu et al, 2016;Lv et al, 2018;Zhu et al, 2016). Recent evidents (Chu et al, 2015;Guo et al, 2019;Sun et al, 2015) have indicated that PKM2 is highly over-expressed in LUAC compared to normal lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Warburg effect, most cancer cells produce energy by glycolysis, suggesting that targeting cancer metabolism might be a potential field in drug discovery (Liu et al, 2016;Lv et al, 2018;Yang et al, 2017). As a key regulator involving in Warburg effect, PKM2 is frequently expressed at high levels in numerous human tumors and play an important role in tumorigenesis, aerobic glycolysis and chemoresistance (Dayton, Jacks & Vander Heiden, 2016;Guo et al, 2019;Liu et al, 2016;Lv et al, 2018;Zhu et al, 2016). Recent evidents (Chu et al, 2015;Guo et al, 2019;Sun et al, 2015) have indicated that PKM2 is highly over-expressed in LUAC compared to normal lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Warburg effect, most cancer cells produce energy by glycolysis, suggesting that targeting cancer metabolism might be a potential field in drug discovery (Liu et al 2016;Lv et al 2018;Yang et al 2017). As a key regulator involving in Warburg effect, PKM2 is frequently expressed at high levels in numerous human tumors, and play an important role in tumorigenesis, aerobic glycolysis and chemoresistance (Dayton et al 2016;Guo et al 2019;Liu et al 2016;Lv et al 2018;Zhu et al 2016). Recent evidents (Chu et al 2015;Guo et al 2019;Sun et al 2015) have indicated that PKM2 is highly over-expressed in LUAC compared to normal lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Given that PKM2 is an important driver regulating energy metabolism of cancer cells, targeting PKM2 might be an promising therapeutic strategy. Recent studies have reported that high PKM2 expression is associated with an unfavorable prognosis in multiple human tumors including hepatocellular carcinoma (Lv et al 2018), breast cancer (Yang et al 2017) and osteosarcoma (Liu et al 2016), etc. Nevertheless, over-expression of PKM2 in gastric cancer and pancreatic cancer were not correlated with poor prognosis (Zhu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These models are typically applied to individual pathways [68,69]. A global reconstruction model of human metabolism is publically available—Recon 2 [70]—this model can be combined with public clinical and experimental gene transcriptome data in order to identify potential metabolic characteristics and thus weaknesses of specific cancer types [71].…”
Section: Cancer-specific Metabolism As a Drug Target Opportunity Amentioning
confidence: 99%